Investigations of the mechanical properties on different print orientations in SLA 3D printed resin. (June 2020) - Saini, JS; Dowling, Luke; Kennedy, John; Trimble, Daniel
3D printing has been recognized as the future manufacturing technique by different industries. The properties of products manufactured using this technique depend upon large number of factors, with print orientation being one among the most important factors. Currently, there is no standard for the build orientation of the printed component. To date, the analysis of material properties is conducted by testing specimens printed in different orientations. The present work explores the effect of layer orientations on the different mechanical properties of an SLA manufactured polymer material. Five different orientations, i.e. 0°, 22.5°, 45°, 67.5° and 90° were used to print the specimens for the analysis of mechanical properties of the material. Tensile, compression, flexural, impact, fatigue and vibration analysis are the different mechanical tests that were conducted as per their respective standards. It was found that the print orientation plays a significant role in the behaviour of the respective mechanical property. The maximum tensile and compressive load are being taken by the specimens printed at an angle of 22.5° and 67.5°, respectively. The specimen printed at 67.5° orientation again have highest flexural strength, whereas the specimen printed at 0° have higher impact and fatigue strength.